Evaluation of gene validity for CPVT and short QT syndrome in sudden arrhythmic death. (24th September 2021) - Walsh, Roddy; Adler, Arnon; Amin, Ahmad S; Abiusi, Emanuela; Care, Melanie; Bikker, Hennie; Amenta, Simona; Feilotter, Harriet; Nannenberg, Eline A; Mazzarotto, Francesco; Trevisan, Valentina; Garcia, John; et al.
Abstract: Aims: Catecholaminergic polymorphic ventricular tachycardia (CPVT) and short QT syndrome (SQTS) are inherited arrhythmogenic disorders that can cause sudden death. Numerous genes have been reported to cause these conditions, but evidence supporting these gene–disease relationships varies considerably. To ensure appropriate utilization of genetic information for CPVT and SQTS patients, we applied an evidence-based reappraisal of previously reported genes. Methods and results: Three teams independently curated all published evidence for 11 CPVT and 9 SQTS implicated genes using the ClinGen gene curation framework. The results were reviewed by a Channelopathy Expert Panel who provided the final classifications. Seven genes had definitive to moderate evidence for disease causation in CPVT, with either autosomal dominant ( RYR2, CALM1, CALM2, CALM3 ) or autosomal recessive ( CASQ2, TRDN, TECRL ) inheritance. Three of the four disputed genes for CPVT ( KCNJ2, PKP2, SCN5A ) were deemed by the Expert Panel to be reported for phenotypes that were not representative of CPVT, while reported variants in a fourth gene ( ANK2 ) were too common in the population to be disease-causing. For SQTS, only one gene ( KCNH2 ) was classified as definitive, with three others ( KCNQ1, KCNJ2, SLC4A3 ) having strong to moderate evidence. The majority of genetic evidence for SQTS genes was derived from very few variants (five in KCNJ2, two in KCNH2, one in KCNQ1 / SLC4A3 ). Conclusions: Seven CPVT and four SQTS genes have valid evidence for disease causation and should be included in genetic testing panels. Additional genes associated with conditions that may mimic clinical features of CPVT/SQTS have potential utility for differential diagnosis. Graphical Abstract: